Partial Cystectomy for Papillary Urothelial Carcinoma in a Dog - Tiwary, Ramesh; Raksha; Kumar, Kaushal; Kumari, Archana; Kumar, Rajesh; Kumar, Ajeet; Aakaksha; Singh, M. K. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during October, 2024 to June, 2025 at the Teaching Veterinary Clinical Complex, Bihar Veterinary College, Patna, Bihar, India. This study evaluated the surgical management of high-grade papillary urothelial carcinoma (UC) in a young Great Dane dog using partial cystectomy combined with ureteral reimplantation. Transitional cell carcinoma (TCC), or urothelial carcinoma, is the most common malignancy of the canine urinary bladder and serves as a relevant model for human bladder cancer. The study involved a three-year-old male Great Dane presented with a history of persistent hematuria and stranguria. Ultrasonographic examination revealed a large, vascular intravesical mass. Based on the clinical signs, history, and ultrasonographic findings, the case was tentatively diagnosed as high-grade papillary urothelial carcinoma, and surgical management was decided. A partial cystectomy was performed, involving excision of approximately 60% of the bladder wall, including part of the trigone and the right ureter, followed by ureteral reimplantation. Histopathological examination confirmed a high-grade papillary UC. Postoperatively, the dog was treated with a broad-spectrum antibiotic for seven days and an analgesic for three days, along with supportive therapy. Recovery was uneventful, and normal urinary function was restored within one week. Tumor recurrence was detected three months post-surgery; however, the dog survived an additional seven months with a good quality of life. The findings suggested that partial cystectomy with ureteral reimplantation was an effective surgical technique for managing high-grade papillary urothelial carcinoma in dogs.